2011
DOI: 10.1016/j.freeradbiomed.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species alter autocrine and paracrine signaling

Abstract: Cytochrome P450 (P450) 3A4 (CYP3A4) is the most abundant P450 protein in human liver and intestine, and is highly inducible by a variety of drugs and other compounds. The P450 catalytic cycle is known to uncouple and release reactive oxygen species (ROS), but the effects of ROS from P450 and other enzymes in the endoplasmic reticulum has been poorly studied from the perspective of effects on cell biology. In this study, we express low levels of CYP3A4 in HepG2 cells, a human hepatocarcinoma cell line, and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
(58 reference statements)
0
10
0
2
Order By: Relevance
“…RONS production is associated with proinflammatory cytokine, antibacterial lectin and Th17 responses RONS production can exert autocrine and paracrine effects [31] on homeostasis and signalling of many cell types, thus promoting local inflammatory reactions and immune reactivity. Accordingly, Il1, Il6, Il18, Il23 and Il17 levels were all high in the ileum of NOD mice fed normal chow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RONS production is associated with proinflammatory cytokine, antibacterial lectin and Th17 responses RONS production can exert autocrine and paracrine effects [31] on homeostasis and signalling of many cell types, thus promoting local inflammatory reactions and immune reactivity. Accordingly, Il1, Il6, Il18, Il23 and Il17 levels were all high in the ileum of NOD mice fed normal chow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next considered signaling mechanisms that could act only on cells intimately close to their origin. Reactive oxygen species (ROS) are unstable signaling molecules, and generally act in an autocrine or paracrine manner 37 . We tested whether ROS in cultured ganglia were responsible for the increase in CT mRNA by adding the antioxidant tempol to the culture media.…”
Section: Resultsmentioning
confidence: 99%
“…We also analyzed a number of secreted proteins reported by others to be produced by normal or cancerous breast tissue. Finally, we evaluated a selection of proteins that we identified as being secreted at higher levels in human mammary cells in response to modest changes in intracellular ROS or to epidermal-growth-factor signaling [8, 9, 22, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS), which are responsible for oxidative protein modifications, regulate important processes in epithelial cancers such as activation of MAPK/Erk and PI3K/Akt pathways [7]. In cultured human mammary epithelial cells, we found that both of these signaling pathways and intracellular ROS regulate the secretion of a variety of autocrine factors, paracrine factors and matrix metalloproteases [8, 9]. Based on these studies, we hypothesized that alterations in cell signaling and oxidative stress associated with breast cancer would not only results in increased levels of certain proteins that are secreted into blood but that these proteins would have unusually high oxidation rates.…”
Section: Introductionmentioning
confidence: 99%